A compartment model and numerical analysis of circulatory economy. Issue 1 (2nd January 2019) - Yang, Zhongzhi; Kong, Pengzhi; Li, Boying; Chao, Bo
Abstract : This paper describes an industrial structure and its equation system of a circular economy for material circulation and builds a system dynamic model for resources recycling utilization based on Compartment Model Theory. A circulation multiplier and its computational formula are defined for measuring the efficiency of resources recycling utilization. The simulated results indicate that the resources recycling utilization can not only realize the amount accumulation of natural resources and improve the resources recycling efficiency but can minimize discharges into natural environment by means of adjustment to each compartment parameter in the circular economy.